Adapting evidence-based intervention in rural tourism policies: pragmatic benchmarking considerations for tourism business operations in Semporna, Sabah, Malaysia - Siow, May Ling; Ramachandran, Sridar; Shuib, Ahmad; Mohammad Afandi, Syamsul Herman (Emerald Group Publishing, 2015)
Purpose: This study aims to assess the possibility of adapting evidence-based policies in the daily operations of tour operators in Semporna, Sabah, Malaysia. This intervention is important, as on-site investigations reveal that operators are operating their businesses with little reference to the ecotourism policy guidelines. Design/methodology/approach: This study adopted a full qualitative approach. In-depth interviews were conducted on tour operators in Semporna, while text mining was used to elicit data from the Malaysian National Ecotourism Plan. Thematic analysis was used to analyse the data from the primary sources. Findings: Gaps were evident between best practices guidelines from the National Ecotourism Plan and the day-to-day practices of tour operators in Semporna, Sabah. This was due to the limitations of the National Ecotourism Plan and the limitations of the operators in identifying and adhering to best practices; the impracticality of best practices in site-specific scenarios; and the benefit of adapting evidence-based practices (ECP) in Semporna, Sabah. Practical implications: The implications of this study include a plan to bring forth a non-parochial and innovative approach in rural tourism policymaking process and to advocate evidence-based intervention through the inclusion and participation of stakeholders. Originality/value: This study contributes towards the requisite of evidence-based intervention for rural tourism policies to meet site-specific needs.